Strength-Cognitive Training: A Systemic Review in Adults and Older Adults, and Guidelines to Promote “Strength Exergaming” Innovations - Esmaeilzadeh, Samad; Kumpulainen, Susanne; Pesola, Arto J. (Frontiers in Psychology, 2022)
Strength-cognitive training: A systemic review in adults and older adults, and guidelines to promote “Strength exergaming” innovations Abstract Background: Despite functional and cognitive benefits, few adults and older adults do strength training twice per week with sufficient intensity. Exercise-based active video games (exergaming) may amplify the cognitive benefits of exercise and increase adherence and motivation towards training. However, the benefits of a well-defined and monitored dose of strength training, executed simultaneously or sequentially with a cognitive element, has received little attention. In this study we have two aims: First, to systematically gather the available evidence; second, to suggest possible ways to promote strength exergaming innovations. Methods: We systematically reviewed randomized controlled trials using simultaneous or sequent combined strength and cognitive training or strength exergaming to improve cognitive or functional outcomes in adults and older adults. Results: After screening 1785 studies (Google Scholar, ACM Digital Library, IEEE Xplore Library, PsycARTICLES, Scopus, Cochrane Library and PubMed) we found three eligible studies. Of the two studies using sequent strength and cognitive training, one showed improved functionality, but the other showed negative effects on cognition. The third study using simultaneous intervention, reported a positive influence on both cognition and function, when compared with either strength training alone or a control group. A moderate level of evidence was showed on GRADE analysis. Conclusion: The existing little evidence suggests that strength and cognitive training improves cognition and function in adults and older adults. The following suggestions may help to promote further innovation: 1) ensure minimal dosage of strength training (30-60min, 2x/week), 2) use machine-based strength training devices to control volume and intensity (to prevent cognitive components from interfering with strength training), 3) include power training by using cognitive tasks requiring rapid reactions, and 4) add cognitive memory tasks (to extend the cognitive benefits of strength training per se), and 5) include motivational exergame elements to increase adherence.